Ti-doped alpha-Fe2O3 by quantum-chemical modeling - Rivera Escobar, R. (2010)
Structure and electronic properties of Ti-doped hematite (?-Fe 2O3) crystal have been studied using a quantum-chemical method based on the Hartree-Fock theory. A supercell model employing a system consisting of 120 atoms has been exploited throughout the investigation. The impurity presence produces defect-inward displacement for the majority of Fe atoms whereas the O atoms experience both defect-inward and defect-outward shifts depending on their original position in the crystal. A small reduction in the band-gap width due to the Ti incorporation is also observed which might lead to some increase in the electrical conductivity in concordance to the available experimental measurements. Two new phenomena are discovered according to results of our modeling, being those of electron density redistribution between different 3d Atomic Orbitals (AOs) within the same Fe atom and extra valence electron escape from the Ti-surrounding region towards far-situated Fe atoms. The latter presumably could explain some contradictory results on saturation magnetization in Ti-doped ?-Fe2O3 compounds. The atomic structure of Ti-doped hematite with pointers indicating lattice relaxation. Ti incorporation into the hematite crystal produces changes upon structural, electronic and electrical properties of this material. © 2010 Elsevier Masson SAS.